2014
DOI: 10.7860/jcdr/2014/8409.4638
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin Resistant Staphylococcus aureus Carriage, Antibiotic Resistance and Molecular Pathogenicity among Healthy Individuals Exposed and Not Exposed to Hospital Environment

Abstract: The nursing students carried MRSA strains similar to those carried by the non-exposed group. Our results suggest that healthcare workers could act as a link and transmit MRSA acquired from the community to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Al evaluar la susceptibilidad antibiótica en el análisis de los estudios realizados, se observó un alto nivel de resistencia de la bacteria a la penicilina (100%, 70%, 92%, 95.3%, 100%, 75%, 100%) en (Krishnamurthy et al, 2014) (Daneli et al, 2020), los cuales permiten observar el alto nivel de resistencia a la Penicilina y la resistencia menor a la tetraciclina, gentamicina eritromicina (<22%). Ello es de esperar a consecuencia del amplio uso y abuso de antibióticos en la población estudiantil.…”
Section: Resultsunclassified
“…Al evaluar la susceptibilidad antibiótica en el análisis de los estudios realizados, se observó un alto nivel de resistencia de la bacteria a la penicilina (100%, 70%, 92%, 95.3%, 100%, 75%, 100%) en (Krishnamurthy et al, 2014) (Daneli et al, 2020), los cuales permiten observar el alto nivel de resistencia a la Penicilina y la resistencia menor a la tetraciclina, gentamicina eritromicina (<22%). Ello es de esperar a consecuencia del amplio uso y abuso de antibióticos en la población estudiantil.…”
Section: Resultsunclassified
“…3,5,7, Regarding the locations of the studies, they were carried out in Brazil, Malaysia, Colombia, China, Palestine, Spain, Brunei, India, Turkey, Czech Republic, Saudi Arabia, Madagascar, Pakistan, Nepal, Tanzania, South Korea, Iran, Ireland, Jordan, Italy, Nigeria, Poland and Ethiopia. 3,5,7,11,12,[14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The populations addressed by the researchers of these 30 studies were nursing students, medical students, health science students and dental students. 3,5,7,[12][13][14][15][16][17][18]20,21,[23][24][25]27,[29]…”
Section: Resultsmentioning
confidence: 99%
“…3,5,7,15-17,18-27-30,33-37 Regarding the prevalence of MRSA, the student population in some studies was divided into groups before exposure to healthcare and after such exposure. 14,19,21,23,26 The percentages found are shown in Table 3. To investigate the prevalence, antimicrobial susceptibility and molecular factors characteristic of CA (community acquired) MRSA among two groups of college students (medical and non-medical).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus is difficult to treat due to its high propensity to develop antibiotic resistance ( Foster, 2017 ). In the decades following its discovery, methicillin resistant S. aureus (MRSA) ( Jevons, 1961 ), which is resistant to β-lactam antibiotics, has been frequently implicated in healthcare-associated infections ( Chambers and DeLeo, 2009 ; Krishnamurthy et al., 2014 ). However, studies have shown the emergence of MRSA transmission and infection in those without previous health-care contact, which is referred to as community-associated MRSA (CA-MRSA) ( DeLeo et al., 2010 ; Udo, 2013 ).…”
Section: Introductionmentioning
confidence: 99%